Menilik Pelaksanaan Program Keselamatan dan Kesehatan Kerja : Fenomena pada Industri Stamping - Hananto, Adiel Amandus; Rahardja, Edy (Diponegoro Journal of Management, 2015)
This study aimed to identify the implementation of occupational safety and health programon an company and then to know the employees perception toward the implementation of occupational safety and health program. In this research the implementation of occupational safetyand  health  programs  viewed  through  the  seven  elements  namely  the  commitment  of  topmanagement, occupational safety and health training, personal protective equipment, supervision, work regulations and work procedures, safety signs and health services.This study use qualitative methods, where data collection is done by the interview. The main informan of this study were the employees from the safety health environment department and as  the  comparative  subject  were  used  from  the    employees  that  worked  in  the  productiondepartment that already finished the training period for three months.Results obtained from this study states that three elements of the implementation of occupational  safety  and  health  program  namely  Commitment  of  Top  Management,  PersonalProtective Equipment and Health Service has been implemented properly and in accordance withwhat is required by employees. While the other four namely Occupational Safety and HealthTraining, Supervision, Work Procedure and Work Regulation, and the Safety Signs has not been properly implemented and still not in accordance with what is required by the employees.